The Essence And Economic Importance Of Labor Standardization Processes In Small Enterprises Producing Sewing And Knitted Products - Abdukhamidov, Abdurakhmon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This work deeply explores the theoretical foundations, practical mechanisms, and the impact of labor standardization processes on production efficiency in small enterprises producing sewing and knitted products. A scientifically based system of labor standardization is analyzed as an important factor in increasing labor productivity, rational use of the workforce, reducing costs, and achieving overall economic stability. The study identifies the impact of labor standardization on efficiency indicators through the analysis of modern approaches, normative-legal frameworks, and existing issues in small sewing and knitted enterprises, and proposes directions for improvement.